Prosedur Polya dalam Pembelajaran Kooperatif TGT untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Siswa Kelas 2 SD - Sandri Sianipar; Hery Winoto Tj; Takim Andriono (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to enhance the motivation and learning outcomes in mathematics for second-grade students at Cita Hati Christian School through the implementation of Polya's procedure in cooperative learning of the Teams Games Tournament (TGT) type in Mathematics lesson. This research uses the classroom action research (CAR) method conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were 22 second-grade students. The instruments used in this study include observation sheets and learning outcome tests. The results of the study indicate that the implementation of Polya's procedure in TGT-type cooperative learning can improve students' motivation and learning outcomes. This is evidenced by the consistent average motivation scores of 100% in both the first and second cycles. Additionally, students' learning outcomes also showed improvement, with the average test scores increasing from 91% in the first cycle to 95% in the second cycle. Thus, it can be concluded that the use of Polya's procedure in TGT-type cooperative learning is effective in enhancing the motivation and learning outcomes in mathematics for second-grade students at Cita Hati Christian School.